Evaluating the Effectiveness of Ahmed Glaucoma Valve Implantation in Reducing Intraocular Pressure in Refractory Glaucoma in the Saudi Arabian Population at a Tertiary Care Centre - Almarzouki, Nawaf (Journal of Contemporary Medical Sciences, 2024)
Objectives: To assess the efficacy of Ahmed glaucoma valve implantation (AGVI) in lowering intraocular pressure (IOP) in patients with refractory glaucoma. Methods: In this retrospective study, we analyzed the medical records of 60 patients who received AGVI for refractory glaucoma. Data collected included demographics, type of glaucoma, preoperative and postoperative IOP, number of glaucoma medications, and any surgical complications. Success was defined as achieving an IOP <21 mmHg at the final follow-up visit. Results: At the final follow-up (mean duration of 11.6 months), AGVI achieved successful IOP control (IOP of <21 mmHg) in 40 eyes (66.7%). The mean number of glaucoma medications decreased significantly from 2.95 preoperatively to 1.98 postoperatively (p < 0.001). Neovascular glaucoma (NVG) had a lower success rate compared to other types of glaucoma. Prior glaucoma surgery was associated with a higher risk of failing to reach target IOP, although this trend was not statistically significant (p = 0.108). Conclusion: AGVI implantation effectively lowered IOP in patients with refractory glaucoma, especially in the short term. However, long-term success rates were lower, and NVG showed less favorable outcomes. AGVI is a valuable option for managing refractory glaucoma, but careful patient selection is essential. Further research is needed to evaluate long-term efficacy and refine treatment strategies.